(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Trapping rats has become a practical and environmentally safe method of control as well as monitoring the presence of rats in a place. The study aims to determine the presence of house rats (Rattus tanezumi Temminck) and the trap success rate around the IPB Darmaga Campus, Bogor, Indonesia, using a single live trap. There were 10 traps installed incrementally over 3 consecutive nights at 10 locations both indoor and outdoor. The number of rats caught, the number of rat footprints, the size and sex of the rats, and the location of the trapped rats became an observed parameter. The results showed that house rats around the IPB Darmaga Campus caused damage to facilities, physical appearance, faeces, and urine odor. The trapping success around the IPB Darmaga Campus from 300 trappings reached 9%, which is 3.67% of trapped rats remained in traps and 5.33% rats escaped from traps. The trapping success was affected by trap shyness by 72.16%.